Environmental Risk Factors on Suicide of Children and Young People - Ann John; Marcos del Pozo Banos; Keith Lloyd (International Journal of Population Data Science, 2018)
Introduction The World Health Organization recognizes suicide as a public health priority. Recent studies have focused on health care contacts for those who complete suicide to highlight opportunities for intervention. In Wales, electronic health records (EHR) are routinely collected, providing an invaluable opportunity for researching suicide risk factors.